A guide to international monetary economics : exchange rate theories, systems and policies - Visser, H. (Cheltenham, UK ; Northhampton, MA : E. Elgar, 2004)
A systematic overview of exchange rate theories, an analysis of exchange rate systems and a discussion of exchange rate policies including discussion of the obstacles that may confront policy-makers while running any particular system. This third edition emphasises recent developments such as the creation and expansion of the Euro and the radical solution of dollarisation. The book is a concise treatment of this complex field and does not encumber the reader with a surfeit of potentially distracting institutional details. As with previous editions, the emphasis is on the economic reasoning behind the formulae while introducing students to the mathematics that will enable them to pursue further reading. This book is aimed at postgraduate and advanced undergraduate students in general and international economics and international finance, as well as business management scholars and researchers specialising in finance.
Includes bibliographical references (p. 221-249) and index.
oif 21/07/14
Loan
Keywords: Foreign exchange; Foreign exchange rates